ICTV Virus Taxonomy Profile: Chrysoviridae. (20th January 2020) - Kotta-Loizou, Ioly; Castón, José R.; Coutts, Robert H. A.; Hillman, Bradley I.; Jiang, Daohong; Kim, Dae-Hyuk; Moriyama, Hiromitsu; Suzuki, Nobuhiro; ,
Abstract : Members of the family Chrysoviridae are isometric, non-enveloped viruses with segmented, linear, dsRNA genomes. There are 3–7 genomic segments, each of which is individually encapsidated. Chrysoviruses infect fungi, plants and possibly insects, and may cause hypovirulence in their fungal hosts. Chrysoviruses have no known vectors and lack an extracellular phase to their replication cycle; they are transmitted via intracellular routes within an individual during hyphal growth, in asexual or sexual spores, or between individuals via hyphal anastomosis. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the family Chrysoviridae, which is available at ictv.global/report/chrysoviridae .